Whey Protein Supplementation Post Resistance Exercise in Elderly Men Induces Changes in Muscle miRNA's Compared to Resistance Exercise Alone - D'Souza, Randall F.; Zeng, Nina; Markworth, James F.; Figueiredo, Vandre C.; Hedges, Christopher P.; Petersen, Aaron C.; Della Gatta, Paul A.; Cameron-Smith, David; Mitchell, Cameron J. (Frontiers in Nutrition, 2019)
Progressive muscle loss with aging results in decreased physical function, frailty, and impaired metabolic health. Deficits in anabolic signalling contribute to an impaired ability for aged skeletal muscle to adapt in response to exercise and protein feeding. One potential contributing mechanism could be exerted by dysregulation of microRNAs (miRNAs). Therefore the aim of this study was to determine if graded protein doses consumed after resistance exercise altered muscle miRNA expression in elderly men. Twenty-three senior men (67.9 ± 0.9 years) performed a bout of resistance exercise and were randomised to consume either a placebo, 20 or 40 g of whey protein (n=8, n=7 and n=8 respectively). Vastus lateralis biopsies were collected before, two and four hours after exercise. Expression of 19 miRNAs, previously identified to influence muscle phenotype, were measured via RT-PCR. Of these, miR-16-5p was altered with exercise in all groups (p=0.032). Expression of miR-15a and -499a increased only in the placebo group 4 hours after exercise and miR-451a expression increased following exercise only in the 40g whey supplementation group. Increased p-P70S6KThr389 and p-AktSer473 following exercise were correlated with alterations in miR-208a and -499a and -206 expression, irrespective of protein dose, suggesting a possible role for miRNA in the regulation of acute phosphorylation events during early hours of exercise recovery.